Cystic versus non-cystic prolactinoma: clinical, hormonal, radiological, and remission outcomes in Basrah - Reman, Khulood Abed; Alidrisi, Haider Ayad; Alhamza, Ali Hussain Ali; Alobaidy, Hassan Falah; Mansour, Abbas Ali (Frontiers in Endocrinology, 2025)
IntroductionProlactinomas are the most common functional pituitary adenomas. Cystic prolactinomas, characterized by substantial cystic components on magnetic resonance imaging (MRI) scans, may exhibit different clinical behaviors and treatment outcomes. The aim of this study was to compare the clinical, hormonal, and radiological characteristics, and identify predictors of remission in patients with cystic versus non-cystic prolactinomas.MethodsThis retrospective cohort study included 196 patients who were diagnosed with prolactinoma between January 2010 and January 2024. The patients were categorized into cystic (n=46) and non-cystic (n=150) groups based on their MRI characteristics. Data on clinical presentation, hormonal levels, imaging findings, treatment response, and remission predictors were analyzed.ResultsPatients with cystic prolactinomas were younger and more likely to experience headaches. Lower follicular stimulating hormone levels were also observed in this group. Clinical symptom improvement over time did not differ significantly between the cystic and non-cystic prolactinomas at any follow-up interval. Prolactin levels declined similarly in both groups, and the percentage of patients who achieved a reduction in adenoma diameter did not differ significantly between the groups at any follow-up period. Remission rate was associated with lower baseline prolactin levels, early tumor shrinkage, and initial transsphenoidal surgery.ConclusionCystic morphology in prolactinomas does not compromise treatment response. Predictors of early remission can guide management strategies. Surgical intervention remains pivotal in selected cases.